Letter to Jane Tolmach from John A. Howard - John A. Howard:::::: (1976)
In a May 17, 1976 letter, attorney John A. Howard wrote to Jane Tolmach after speaking with her at Villanova Preparatory School in Ojai. He enclosed a $100 contribution to her Assembly campaign. Howard expressed hope that she would be successful in the June 8 primary and become the Democratic nominee in the November election.